Regulation of Cathelicidin Antimicrobial Peptide (CAMP) Gene Expression by TNFa and cfDNA in Adipocytes - Höpfinger, Alexandra; Schmid, Andreas; Schweitzer, Leonie; Patz, Marissa; Weber, Anja; Schäffler, Andreas; Karrasch, Thomas; Justus Liebig University Giessen (My University, 2023)
Understanding the complex interactions between metabolism and the immune system (“metaflammation”) is crucial for the identification of key immunomodulatory factors as potential therapeutic targets in obesity and in cardiovascular diseases. Cathelicidin antimicrobial peptide (CAMP) is an important factor of innate immunity and is expressed in adipocytes. CAMP, therefore, might play a role as an adipokine in metaflammation and adipose inflammation. TNFα, cell-free nucleic acids (cfDNA), and toll-like receptor (TLR) 9 are components of the innate immune system and are functionally active in adipose tissue. The aim of the present study was to investigate the impact of TNFα and cfDNA on CAMP expression in adipocytes. Since cfDNA acts as a physiological TLR9 agonist, we additionally investigated TLR9-mediated CAMP regulation in adipocytes and adipose tissue. CAMP gene expression in murine 3T3-L1 and human SGBS adipocytes and in murine and human adipose tissues was quantified by real-time PCR. Adipocyte inflammation was induced in vitro by TNFα and cfDNA stimulation. Serum CAMP concentrations in TLR9 knockout (KO) and in wildtype mice were quantified by ELISA. In primary adipocytes of wildtype and TLR9 KO mice, CAMP gene expression was quantified by real-time PCR. CAMP gene expression was considerably increased in 3T3-L1 and SGBS adipocytes during differentiation. TNFα significantly induced CAMP gene expression in mature adipocytes, which was effectively antagonized by inhibition of PI3K signaling. Cell-free nucleic acids (cfDNA) significantly impaired CAMP gene expression, whereas synthetic agonistic and antagonistic TLR9 ligands had no effect. CAMP and TLR9 gene expression were correlated positively in murine and human subcutaneous but not in intra-abdominal/visceral adipose tissues. Male TLR9 knockout mice exhibited lower systemic CAMP concentrations than wildtype mice. CAMP gene expression levels in primary adipocytes did not significantly differ between wildtype and TLR9 KO mice. These findings suggest a regulatory role of inflammatory mediators, such as TNFα and cfDNA, in adipocytic CAMP expression as a novel putative molecular mechanism in adipose tissue innate immunity.
Keywords: ddc:610